Research progress on ferroptosis in Myelodysplastic syndromes - Yang, Yifan; Han, Jiongping; Wei, Yuxin; Jin, Jiacheng; Feng, Weiying (Frontiers in Pharmacology, 2025)
Myelodysplastic syndromes (MDS) are a group of malignancies characterized by clonal proliferation of hematopoietic stem cells, ineffective hematopoiesis, peripheral cytopenias, and a high risk of transformation to acute myeloid leukemia. Current therapeutic strategies for MDS have limited efficacy. Thus, identifying new therapeutic targets and prognostic biomarkers is a critical future research direction. Ferroptosis, a new type of iron-dependent programmed cell death, has become a recent hotspot in the field of oncology research. Recent results have demonstrated that iron metabolism, lipid metabolism, and other pathways can be targeted to induce ferroptosis in MDS cells. In addition, ferroptosis-related genes are of significance in the prognosis and diagnosis of MDS. This article reviews the current research progress on ferroptosis in MDS, including its potential for targeting as a therapeutic intervention strategy.